BIOCOMPATIBILITY OF TITANIUM IMPLANTS COATED WITH BIOCOMPOSITE IN A RAT MODEL OF FEMORAL FRACTURE - OLTEAN-DAN, Daniel; FRANGOPOL, †Petre T.; BALINT, Reka; TOMOAIA, Gheorghe; MOCANU, Aurora; TOMOAIA-COTISEL, Maria (Studia Universitatis Babeș-Bolyai Chemia, 2021)
The biocompatibility of uncoated titanium, Ti, nails and coated with an innovative biocomposite is assessed in a rat model of femoral fracture. The biocomposite is based on multi-substituted hydroxyapatite, ms-HAP containing Mg, Zn and Si, and is used as a coating material deposited on Ti implants, due to the excellent biocompatibility and osteoconductive property of ms-HAP. Specific focus has been given to biocomposite coating made of ms-HAP functionalized with collagen (ms-HAP/COL, core/shell nanoparticles) NPs embedded into poly lactic acid, PLA, matrix and finally covered by COL layer. This coating on Ti implants is noted as ms-HAP/COL@PLA/COL and named HAPc, and is characterized by SEM images and EDX spectra. Twenty-four Wistar albino rats with left femoral fracture, were used and divided in two equal groups, namely the control group, CG, with uncoated Ti implants and HAPc rat group with Ti implants coated with HAPc biocomposite through layer-by-layer, LBL, dip coating technique. After two- and eight-weeks post-surgery, they were evaluated by bone markers serum concentration, micro-CT and histological study. The alkaline phosphatase (ALP) and osteocalcin (OCN) expression, in the HAPc group showed higher values with an osteoblastic activity more intense and a more advanced callus stage. The micro-CT results showed that biocomposite coating significantly increased the bone volume/ tissue volume (BV/TV). The most advanced stage of bone remodelling with osseointegration of the Ti implants was observed in HAPc group, where the new formed trabecular bone is almost completely replaced by compact bone. This study provides a novel strategy for the treatment of bone fracture with a superior osseointegration of biocomposite coated Ti implants and potential orthopaedic applications.